2012
DOI: 10.1371/journal.pone.0040150
|View full text |Cite
|
Sign up to set email alerts
|

FLP Recombinase-Mediated Site-Specific Recombination in Silkworm, Bombyx mori

Abstract: A comprehensive understanding of gene function and the production of site-specific genetically modified mutants are two major goals of genetic engineering in the post-genomic era. Although site-specific recombination systems have been powerful tools for genome manipulation of many organisms, they have not yet been established for use in the manipulation of the silkworm Bombyx mori genome. In this study, we achieved site-specific excision of a target gene at predefined chromosomal sites in the silkworm using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…The FLP/FRT systems can reportedly mediate site-specific DNA excision and integration in cultured silkworm cells and B. mori [14,17]. Recently, Cre-lox recombinase has also been demonstrated to work in the silkworm [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The FLP/FRT systems can reportedly mediate site-specific DNA excision and integration in cultured silkworm cells and B. mori [14,17]. Recently, Cre-lox recombinase has also been demonstrated to work in the silkworm [16].…”
Section: Discussionmentioning
confidence: 99%
“…Although the most commonly used site-specific integrases for genetic manipulation are Cre and FLP, it has been reported that the recombination efficiency is lower when compared with the uC31/att system [5,17,33]. Hence, uC31 integrase is regarded as the best potential tool for transgenesis applications and therapeutic gene transfer [34,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This allows for repeated transgene integration into a site in the genome that will result in predictable transgene expression. These systems have been successfully used in B. mori [19][20][21] although the recombination efficiency has been very low compared with efficiencies seen in other organisms such as Drosophila. Although potentially useful in B. mori, improvements are needed in the performance of these site-specific recombination systems to make them practical options for those working with this species.…”
Section: Transposon-based Technologies (A) Transgene Integration Techmentioning
confidence: 99%
“…These shortcomings could be overcome by utilizing transgenic (Tg), knockin (KI), and knockout (KO) mouse models, collectively known as genetically engineered mouse (GEM) models. Cre-Lox and Flp-FRT recombination systems are the most commonly used approaches for the development of conditional and inducible KO and KI mouse models [27, 28]. Some of the mucin mouse models have provided crucial information about the importance of mucins including their role under physiological and pathological conditions.…”
Section: Introductionmentioning
confidence: 99%